Physiology-Based Revascularization of Left Main Coronary Artery Disease. (11th February 2021) - Kayaert, Peter; Coeman, Mathieu; Gevaert, Sofie; De Pauw, Michel; Haine, Steven
Abstract : It is of critical importance to correctly assess the significance of a left main lesion. Underestimation of significance beholds the risk of inappropriate deferral of revascularization, whereas overestimation may trigger major but unnecessary interventions. This article addresses the invasive physiological assessment of left main disease and its role in deciding upon revascularization. It mainly focuses on the available evidence for fractional flow reserve and instantaneous wave-free ratio, their interpretation, and limitations. We also discuss alternative invasive physiological indices and imaging, as well as the link between physiology, ischemia, and prognosis.